2014
DOI: 10.1177/0971685814539407
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Spirituality Facilitation: A Person–Organization Fit Approach

Abstract: The article proposes a framework utilizing the Person-Organization (P-O) fit approach to facilitate spirituality in the workplace. The article argues that spirituality can be described on a continuum varying from low to high at both individual and organizational levels. The interaction of the two continuums is then used to suggest a model to facilitate workplace spirituality. Thus, the approach is to first consider the interaction of person (individual) and situation (organization) factors and then depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 50 publications
(74 reference statements)
0
13
0
2
Order By: Relevance
“…PO fit theory refers to compatibility between people and organizations (Kristof, 1996); the greater the compatibility between an individual and organization (i.e., needs and values), the more likely outcomes such as an individual's perceived need for meaning and purpose can occur. The complementary needssupply perspective of PO fit theory, where fit occurs 'when an organization satisfies individuals' needs, desires, or preferences' (Kristof, 1996, p. 3), offers a first step to integrating workplace spirituality into a more traditional framework of investigation (Ashforth & Pratt, 2003;Sheep, 2004Sheep, , 2006Singhal, 2007;Singhal & Chatterjee, 2006;Vallabh & Singhal, 2014). Singhal and Chatterjee (2006), for example, offer a framework built on the needs-supply perspective of PO fit to examine the antecedent factors and interactive effects of personal and workplace spirituality and subsequent outcomes.…”
Section: Po Fit Theorymentioning
confidence: 99%
“…PO fit theory refers to compatibility between people and organizations (Kristof, 1996); the greater the compatibility between an individual and organization (i.e., needs and values), the more likely outcomes such as an individual's perceived need for meaning and purpose can occur. The complementary needssupply perspective of PO fit theory, where fit occurs 'when an organization satisfies individuals' needs, desires, or preferences' (Kristof, 1996, p. 3), offers a first step to integrating workplace spirituality into a more traditional framework of investigation (Ashforth & Pratt, 2003;Sheep, 2004Sheep, , 2006Singhal, 2007;Singhal & Chatterjee, 2006;Vallabh & Singhal, 2014). Singhal and Chatterjee (2006), for example, offer a framework built on the needs-supply perspective of PO fit to examine the antecedent factors and interactive effects of personal and workplace spirituality and subsequent outcomes.…”
Section: Po Fit Theorymentioning
confidence: 99%
“…The individual will think in more productive direction, welfare for others, growing with others and with team spirit. Therefore, at workplace an employee full of spirituality is when happy will make the culture of the organization always conducive (Vallabh & Singhal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Do core human values reinforce prosocial behaviour on a global scale? A large body of work in cognitive and organizational psychology, management, sociology and related disciplines has demonstrated that personal values predict various forms of prosocial behaviour (Batson, 1991; Bond & Chi, 1997; Caprara, Alessandri, & Eisenberg, 2012; Caprara & Steca, 2007; Eisenberg & Fabes, 1998; Hitlin, 2007; Oliner & Oliner, 1988; Omoto & Snyder, 1995; Sarangi & Kartha, 2013; Schwartz, 2010; Schwartz & Howard, 1984; Vallabh & Singhal, 2014), defined as actions undertaken to benefit and help others (Batson, 1998; Penner, Dovidio, Piliavin, & Schroeder, 2005). However, there has been no examination of whether values reinforce prosocial behaviour on a global scale.…”
Section: Introductionmentioning
confidence: 99%